2012
DOI: 10.1371/journal.pone.0039348
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin Is Involved in the Entry of Coxiella burnetii into Non-Phagocytic Cells

Abstract: Background Cortactin is a key regulator of the actin cytoskeleton and is involved in pathogen-host cell interactions. Numerous pathogens exploit the phagocytic process and actin cytoskeleton to infect host cells. Coxiella burnetii , the etiologic agent of Q fever, is internalized by host cells through a molecular mechanism that is poorly understood. Methodology/Principal Finding Here we analyzed the role of different cortactin motifs in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…37 Previous studies have also shown that MAPKs are utilized by vertebrates to signal the presence of C. burnetii . 61,8285 Furthermore, MAPKs of Saccharomyces cerevisiae yeast are modulated by C. burnetii ’s Icm/Dot type IVB secretion system effector proteins. 86 …”
Section: Resultsmentioning
confidence: 99%
“…37 Previous studies have also shown that MAPKs are utilized by vertebrates to signal the presence of C. burnetii . 61,8285 Furthermore, MAPKs of Saccharomyces cerevisiae yeast are modulated by C. burnetii ’s Icm/Dot type IVB secretion system effector proteins. 86 …”
Section: Resultsmentioning
confidence: 99%
“…Although SFK phosphorylation of cortactin is important in host invasion by Shigella spp., Staphylococcus aureus and Neisseria meningitidis (Hoffmann et al, 2001;Bougnères et al, 2004;Agerer et al, 2005), several recent reports have depicted involvement of serine phosphorylation of cortactin in pathogen internalization. ERK phosphorylation and SFK dephosphorylation of cortactin are important in HeLa cell invasion by Coxiella burnetii and for cortactin capacity to bind N-WASP (Rosales et al, 2012). Similarly, Campylobacter jejuni induces and requires cortactin phosphorylation by ERK, but not by SFK, and host cell invasion is inhibited in cells depleted of cortactin and N-WASP (Samuelson and Konkel, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…RhoA appears particularly important considering the activity of the downstream effectors ROCK, a protein kinase and mDia1, an actin nucleating factor, are required for optimal internalization [53]. Src-family kinases [54] and the F-actin binding protein cortactin [55] also play roles in internalization of Coxiella by p hagocytic and nonphagocytic cells, respectively.…”
Section: Making a Home In Host Cellsmentioning
confidence: 99%